ANALISIS KETERLAKSANAAN PROBLEM BASED LEARNING BERBANTUAN MULTIMEDIA PEMBELAJARAN LARUTAN ASAM BASA TERHADAP KETERAMPILAN MEMECAHKAN MASALAH - Dian Indah Lestari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
AbstractThis study aims to determine the extent of problem-based learning model implementation assisted instruction multimedia with the type of strategic performance problems in improving students’ problem solving skills on acidic and alkaline materials. The approach used in this research is mixed approach (mix method) with a sequential exploratory model type (model sequence of discovery). The sampling technique is done by purposive sampling. The instrument of research is in the form of observation sheet implementation of problem-based learning model both from teachers and students and also student essay test. The correlation of problem-based learning model implementation with students’ problem solving skill is sought with product moment. The implementation of problem-based learning model by teachers and students has been done according to the principle of problem-based learning model of each meeting. The implementation of problem-based learning model by students with average percentage of 88,44% and ability to solve student problem with average percentage of 69,02%. The correlation of problem-based learning model implementation assisted instruction multimedia of acid-base solution with the problem solving skill is categorized by mediocre with average of 0.43. It can be concluded that the problem-based learning model assisted instruction multimedia acid-base learning in class XI MIA 1 SMA Islam Al-Falah Kota Jambi has been implemented well by teachers and students and also the problem solving skills of students have emerged. Keywords: Problem Based Learning, Multimedia, Strategic Permofance, Problem Solving, Acid and Alkaline